(untitled) (Journal of Computational Mathematics, 1998)
The purpose of this paper is to propose and study a class of quasi-interpolating operators in multivariate spline space S_2^1 (Δ_mn^2*) on non-uniform type-2 triangulation. Based on the operators, we construct cubature formula for two-dimensional hypersingular integrals. Some computing work have been done and the results are quite satisfactory.